Portrait of Patricia and Vince Whiting
Vince and Patricia Whiting sitting in Elvis Presley's bungalow from the movie Blue Hawaii located at the Coco Palms Hotel in Hawaii. Although the date on the verso of the photograph states "1968," based on other photographs in the file the date is discerned as 1988.